Pengaruh Dukungan Keluarga Terhadap Fase Kecemasan Pada Anak Usia Toddler Akibat Hospitalisasi Di RSUD Pandan Arang Boyolali - Utomo, I'in Syukriyani, Siti Arifah, S.Kp., M.Kes, Endang Zulaicha Susilaningsih, S.Kp (2014)
Anxiety witch large most notably when a new children was first admitted to hospitalization and treated. The effect family support can minimize the cause of anxiety. Based on observations and interview counducted found children look happy when accompined by their perent and some cried, inactive and bad mood. The objective is aim to know effect of family support to anxiety phase to toddler children as s result of hospitalization at RSUD Pandan Arang Boyolali. The kind of research was a quantitative, non experimental. The research method was using cross sectional approach. Sampel was (35) parent. Taking simpel was using total sampling. Instrument research was using questionnaires and survey to look family support to anxiety phase to toddler. Data analisis was using chi- square test. (1) Results of research data family support 31 respondent or (89%), (2) phase of protest 17 respondent or (48,6%), phase despair 11 respondent or (31,4%), release phase 7 respondent or (20,0%). With the emergence of anxiety phase toddler age children during hospitalization. Results obstained Chi Square x ² = 9, 084 with p = 0.011. So it decision was Ho be accepted, means the effect of family support to anxiety phase to toddler children as s result of hospitalization with release phase and phase despair.